Selective carbon-phosphorus bond cleavage: expanding the toolbox for accessing bulky divalent lanthanoid sandwich complexes. Issue 27 (16th March 2022) - Shephard, Angus C. G.; Daniels, Daisy P.; Deacon, Glen B.; Guo, Zhifang; Jaroschik, Florian; Junk, Peter C.
Abstract : Tetra- and penta-phenyl cyclopentadienyldiphenylphosphine pro-ligands have been synthesised, which undergo selective C–P bond cleavage with lanthanoid metals (Ln = Eu, Sm and Yb), providing a new route to divalent octa- and deca-phenylmetallocenes. Abstract : The synthesis of two new tetra- and penta-phenycyclopentadienyldiphenylphosphine pro-ligands which readily undergo selective C–P bond cleavage has allowed for the facile synthesis of bulky divalent octa- and deca-phenylmetallocenes of europium, ytterbium and samarium.